ANALISIS PENGARUH PENDAPATAN ASLI DAERAH TERHADAP PERKEMBANGAN PEMBANGUNAN DI PROVINSI ACEH,SUMATERA UTARA, RIAU DAN SUMATERA BARAT - PADANG, NOVI NATALIA; LUMBAN GAOL, ROMASI (UNIKA Santo Thomas, 2022)
The purpose of this study was to determine and analyze the effect of local revenue on development in the provinces of Aceh, North Sumatra, Riau and West Sumatra. The population of this study is the Provinces of Aceh, North Sumatra, Riau and West Sumatra with the observation year 2010 to 2017. The sample was selected using the saturated sample method. The data was processed using the panel data regression statistical test method. The results of this study prove that based on the simultaneous test results, regional taxes, regional levies, separated regional wealth results, other valid PAD simultaneously, have a significant effect on the GRDP variable.